Optimalisasi Fosfat untuk Meningkatkan Pertumbuhan Kerapatan Populasi dan Kemampuan Antagonis Saccharomyces cerevisiae terhadap Fusarium sp. - Hardianto -; Anton Muhibuddin; Antok Wahyu Sektiono (SAINTEKBU, 2018)
Saccharomyces cerevisiae is a common yeast used as a fermenter in the home industry. This yeast is able to grow in media like waste materials. One of the waste materials that can be used as a medium of yeast growth is waste of coconut water. The use of coconut water as a medium of yeast propagation has been widely used in some types of yeasts. The intake of nutrients such as phosphate will make the yeast cells begin to grow and work faster. The yeast cell takes phosphate as ATP. Khamir will turn it into a phosphate polymerization form that is often found within the mitochondria of these cells. S. cerevisiae has the ability not only in terms of fermentation but also can perform other functions in the biological control process. The main methods of this study include the growth test of S. cerevisiae with the addition of a phosphate (KH2PO4), S. cerevisiae growth test by aerator method, yeast antagonist test. The results showed that S. cerevisiae was able to grow higher with the addition of phosphate nutrients (0.5% KH2PO4). This yeast has the potential to control Fusarium sp. The percentage of inhibition was isolate A0 (9,67%), A1 (11%), A2 (10,67%), A3 (12%), A4 (13%), and A5 (6%). Keywords: Yeast, phosphate nutrient, biological control, Fusarium sp.